Swedish rural depopulation - Söderberg, Emma (2015)
About half of the municipalities in Sweden are experiencing a demographic decline and most of these are rural. With continuous urbanization, they are losing both social and economic capital. Social capital is lost if few of the inhabitants can, or want to, stay. This leads to a diminishing tax base and loss of potential to provide sufficient public services, which could lead to even more people deciding to leave. This thesis addresses the strategies and actions taken by municipal leadership in order to adapt to rural depopulation. I have conducted a qualitative investigation in three municipalities in the rural mining region Bergslagen. The region was once the heartland of emerging Swedish industrialization. The three municipalities chosen, Hedemora, Hofors and Smedjebacken, have all experienced a demographic decline of more than 10 % since 1990. Mainly through interviews I have tried to find out what capacities and assets are needed to counteract rural depopulation and how the political and bureaucratic leadership act so as to accomplish this. Have any long-term adaptive strategies to handle depopulation been formulated? The key finding of this study is that none of the chosen municipalities have any long-term strategies to adapt to a declining population. Instead I was able to identify implicit short-term adaptive strategies in the following categories: place marketing, free-time activities, affordable housing, commuting, shutting down schools, demolition of buildings, geriatric care, collaboration and future municipality mergers. The unique occurrences in this study were how the interviewees perceived their situation differently.